Initial experience in the treatment of Peyronie's disease using testicular vaginal tunica graft. (May 2023) - Rico, Luis; Villasante, Nicolás; Blas, Leandro; Bonnano, Nicolás; Ameri, Carlos
Background: Peyronie's disease (PD) is a progressive disorder of the connective tissue of the tunica albuginea of the penis that produces an abnormal curvature, painful erections and different degrees of erectile dysfunction (ED). The aim of this study is to evaluate our initial experience in the surgical treatment of PD using an autologous graft of testicular vaginal tunica. Materials and methods: A retrospective study of 23 patients was carried out between 2015 and 2019. The successful surgical stretching rate was defined as a functional 20 degrees of curvature or less. Postoperative sexual function and complications rate were evaluated as secondary objectives. We used the abbreviated IIEF-5 questionnaire and evaluated the sexual function before and after the surgical procedure. Wilcoxon signed-rank test for paired samples (U test) was used, considering a value of p <0.05 to be statistically significant. Results: Only one patient presented a recurrence of the penile curvature, resulting in a 95.6% success rate of functional stretching. We observed a 1.6 and 0.9 difference between pre- and postoperative total score and satisfaction ( p = 0.002 and p = 0.003 respectively) Conclusion: In this series, the use of testicular vaginal tunic was found to be safe and effective with a significant change in the quality of sexual life, especially reflected in the overall satisfaction after the procedure and a low rate of complications. Level of evidence: Not applicable for this multicentre audit.